Key Concerns on Petroleum Proved Reserves Evaluation in Different Development Stage for International Cooperated Assets under SEC Rules. (March 2019) - Yi, Yanjing; Yang, Hua; Yi, Jie; Yuan, Ruie; Wang, Zhongsheng; Shao, Xinjun; Liu, Qian; Fa, Guifang; Xia, Mingjun; Cai, Dechao
Abstract: The petroleum proved reserves estimation of companies listed in American stock market must follow the SEC rules. However, there are no specified guidelines on the reserves evaluation besides the issued general regulations. This paper presents the procedures and key concerns for sub-classification of proved reserves in different development stages which are summarized from many practical cases. The important concerns include the well test data, initial well productivity, recoverable volumes assessment, five-year development workload and investment, reservoir connectivity, evaluation unit classification, historical performance identification, infill wells recognition, operating cost split, abandonment cost, etc. This study can provide a meaningful reference for SEC reserves evaluation and assets transaction in petroleum industry.